Exploring TiO2-PP as a Reusable Floating Photocatalyst for Humic Acid and Iron Removal in Peat Water - Bintoro Siswo Nugroho; Asifa Asri; Yudha Arman (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
In this study, we fabricate TiO2-PP catalyst and analyze its use for peat water photodegradation. The photocatalyst is a thin layer of TiO2 deposited on the surface of polypropylene (PP) grains by the thermal milling method. Scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDS) images indicate that the fabrication successfully deposited TiO2 particles on the PP grain surface homogeneously well. The results show that photocatalysis of peat water using TiO2-PP with solar irradiation is more effective than the UV lamp. After photocatalysis for 40 hours with solar irradiation, the humic acid content in peat water decreases significantly, accompanied by a decrease in Fe concentration. When being reused, TiO2-PP photocatalyst shows performance above 92% in the fourth iteration, while in the fifth iteration, the performance decreases to 83%. These results show that TiO2-PP has the potential to be applied as a reusable floating photocatalyst to reduce the humic acid and iron content in peat water.